Maintaining Integrity and Professionalism: The Role of Islamic Organizational Behavior in the Management of Islamic Educational Institutions - Okta Iwan Saputra; Iis Susanti; Nirva Diana; Eti Hadiati; Muhammad Safdar Bhatti (Maharot : Journal of Islamic Education, 2026)
Islamic educational institutions are increasingly required to maintain managerial professionalism while preserving Islamic spiritual and ethical values in institutional governance. This study aims to conceptualize Islamic Organizational Behavior (IOB) as a value-based management framework that strengthens integrity, professionalism, and organizational quality in Islamic educational institutions. Employing a qualitative library research design, this study analyzed 29 selected studies published between 2020 and 2025 through a PRISMA-based narrative literature review and thematic content analysis. The findings reveal that Islamic Organizational Behavior is constructed through the integration of Islamic ethical values, Islamic Work Ethics, prophetic leadership, collective synergy, and value-based organizational culture. These elements are further synthesized into four integrative dimensions: spiritual orientation, ethical conduct, collective synergy, and managerial performance. The study demonstrates that values such as iman, ibadah, barakah, amanah, ‘adl, ihsan, shura, ukhuwah, and ta‘awun function not only as normative religious principles but also as operational foundations for leadership, decision-making, collaboration, work ethics, and quality management. This study concludes that Islamic Organizational Behavior offers an integrative framework that bridges Islamic moral-spiritual values and modern organizational behavior theory. The implication of this study is that Islamic educational institutions should systematically translate Islamic values into governance policies, prophetic leadership development, ethical human resource management, and sustainable quality improvement.